The Interplay of Firm, Industry, and Macroeconomic Factors in the Stock Returns of the Non-Financial Sector in Nepal - Khadka, Srijana; Khadka, Ajya Kumar (International Research Journal of MMC, 2023)
This research paper focused on the impact of firm-specific, industry-specific, and macroeconomic variables as it examined the dynamics of stock returns in the Nepalese non-financial sector. The study incorporated a comprehensive analysis of existing literature, methodology, and empirical findings from various studies conducted in Nepal and other countries. Five hydropower companies were the sample of the study. Pearson correlation result showed a negative correlation with a strong inverse relationship between the tangibility of a firm's assets and its stock returns. A significant negative correlation with inflation indicates a moderate inverse relationship between the inflation rate and stock returns. Regression results showed that companies' asset tangibility significantly impacts stock return. Firm size and gross domestic product did not have a statistically significant effect on stock return. However, the inflation rate and exchange rate significantly impacted stock return. Based on the study's findings, policymakers can consider implementing measures to promote a conducive environment for stock market development. This may include improving corporate governance frameworks, enhancing transparency and disclosure requirements, facilitating investor education programs, and ensuring macroeconomic stability through sound monetary and fiscal policies.